The pleasure of inhabiting myself: body expression focused on sensuality, burlesque and pedagogy to heal from the stage. (The Voz a Vos Bulletin, 2025)
This article explores body language focused on sensuality and therapeutic burlesque as pedagogical, artistic, and therapeutic tools for reframing trauma, building self-esteem and identity in older women who have experienced rejection in different areas (emotional, family, social, school, work), generating profound impacts on their relationship with their bodies, self-esteem, self-image, and sensuality. This reflection stems from the life story of Paula Andrea Beltran Garzon. From a critical and sensitive perspective, it aims to highlight how the performing arts and alternative body pedagogies can offer paths to self-discovery, emotional liberation, and individual and social transformation.
Keywords: Therapeutic burlesque; Body expression; Redefining trauma